Effects of Hypertrophy Exercise in Bone Turnover Markers and Structure in Growing Male Rats - Nebot, Elena; Aparicio, Virginia A.; Pietschmann, Peter; Camiletti-Moirón, Daniel; Kapravelou, Garyfallia; Erben, Reinhold G.; Martínez, Rosario; Sánchez-González, Cristina; Porres, Jesús M.; Llopis, Juan; López-Jurado, María; Aranda, Pilar (International Journal of Sports Medicine, 2017)
The benefits of exercise on bone density, structure and turnover markers are rather controversial. The present study aimed to examine the effects of hypertrophy exercise (HE) on bone. 20 male Wistar rats were randomly distributed in 2 experimental groups, one performing HE and the other untrained over 12 weeks. Plasma parameters, bone mineral content, bone mineral density (BMD), structure, and trabecular and cortical microarchitecture were measured. Femur Mg content was 12% higher (p<0.001), whereas femur length, dry weight, P content, and aminoterminal propeptides of type I procollagen were lower in the HE group (all, p<0.05). Total BMD and cortical/subcortical BMD were higher (both, p<0.01), whereas total cross-sectional and trabecular areas were lower (both, p<0.001), and cortical area and thickness were lower in the HE (both, p<0.05). Trabecular connectivity density, number, mean density of total and bone volume were higher in the HE (all, p<0.05). Cortical volume fraction and the mean density of total volume of the diaphysis were lower, whereas the cortical volume density was higher in the HE (all, p<0.05). This HE protocol may have beneficial effect on cancellous bone microarchitecture, but it induces low bone formation and is associated with hypogonadism in growing male rats. However, this type of training might be inefficient to maintain appropriate cortical thickness.
Keywords: bone metabolism; bone mineral density (BMD); training; micro-CT; pQCT